Study On The Characteristic Of Marine Dredged Sediment At Lumut Using Admixture - Prakas, Kumaravelu (Universiti Sains Malaysia, 2017)
Dredge marine sediment commonly extracted from the marine every annum via dredging process. In Malaysia dredge sediment considered as a waste material and this material dump back at sea shore or dumping site after dredging works. Dredge material can beneficially use depending their characteristic, hence this study to determine the characteristic of dredge marine sediment using admixture. Physical and chemical characteristic of dredge marine sediment is carried using the dredge sample taken from Terminal Jetty Lumut Perak and its compared to previous study carried at Lumut (Perak), Marina (Melaka) and Tok Bali (Kelantan). This sample stabilized using ordinary Portland cement (OPC) and chemical foam, hence strength measurement test such as cube compression test and tensile split test carried. The physical characteristic determined and its considered as well graded sand and different with previous study. The chemical characteristic shown a lot of chemical compound found in this sample such as silica, aluminium and also gold oxide found. The mixture of dredge marine sediment with OPC to produce pave walk didn’t give a good results, and mixture of dredge sample with Foam didn’t work out, hence some recommendation given to make sure perfect mixture of pave walk produced such as mixing lime and kaolin in this sample and using geotechnical strength testing such as unconfined compression test to determine the strength of this material.